Estudo experimental e teórico de um resfriador de água por adsorção usando energia solar - Vieira, Herbert Melo (2013)
The respective thesis aims to develop a cooling system that uses an adsorptive chiller for cooling water and subsequent use of this cold water for air conditioning environment, theoretically and experimentally verifying the performance of adsorption refrigeration system, these devices have several advantages, among them, the use of clean energy such as solar. Brazil is a country with high rates of stroke, with an average capacity 16-20 MJ / year / h, so it becomes quite conducive to harnessing this energy, and to be contributing to the reduction of fossil fuel consumption and reduction of harmful gases to the environment. The proposed system consists of flat solar collectors, which are used to convert solar energy into thermal, being last transferred to a heat transfer fluid that circulates through the collector which is then stored in a boiler, or a thermal fluid, to be used whenever required for heating the bed adsorptive a chiller, which is composed of bed adsorptive the finned annular ducts involved with the adsorbent (silica gel). Many studies have been developed with the aim of increasing the performance of these systems, these studies have focused primarily on increasing the mass transfer and heat of adsorption beds and using systems which run continuously through the use of two adsorption beds which work in different phases. Experimental studies in porous beds featuring different configurations were performed, observing thus which present higher rates adsorbent, and subsequently applied this setting in the construction of the porous bed adsorptive chiller. A computational model was developed theoretically allowing you to check your system's performance.